Unemployment and gender equality within the family in Portugal - Coelho, Lina (2015)
This paper analyses the impact of unemployment on the gender division of household work. A sample of 643 dual full-time employed couples and 160 with an unemployed partner was considered. Variance analysis and chi-square tests were performed to analyse the differential impact of the spouses’ employment status on the time devoted to domestic and parental work and on the division of household chores among partners. Results show that male unemployment increases men’s participation in domestic work only on weekdays while female unemployment constrains women into domestic activities both on week and weekend days. Gender patterns of task division also showed to relate significantly to partners’ employment status.